Penerapan Model Pembelajaran Picture And Picture Untuk Meningkatkan Kemampuan Menulis Karangan Deskripsi - I Nyoman Gunaya (Jayapangus Press, 2021)
This classroom action research aims to improve the ability to write descriptive essays for fifth grade students in the first semester of SD Negeri 1 Tejakula in the 2019/2020 school year through the application of the ficture and ficture learning model. This research was conducted in 2 cycles. The design of each cycle consists of planning, implementing, observing / evaluating and reflecting. The research subjects used were the fifth grade students of SD Negeri 1 Tejakula which provided 25 student. Data were analyzed using descriptive statistics. Based on the data obtained, it can be shown that the application of the learning model of pictures and pictures can improve the ability to write descriptive essays for fifth grade students of SD Negeri 1 Tejakula, starting from pre-cycle 64.00% which is classified, cycle I of 69.00% which is classified as sufficient and increased again in the second cycle of 76.40% which is classified as good